Multi-scale data reveal a CD24(+) MUCL1(+) tumor subgroup associated with unfavorable prognosis in ER+ breast cancer - Li, Yingxi; Cao, Junming; Hai, Linyue; Zeng, Jing; Tian, Dongchen; Yu, Yue; Chen, Zhaohui; Tian, Yao (Frontiers in Immunology, 2025)
ObjectiveBreast cancer remains the leading cause of cancer-associated death for women globally. For the group of ER+ breast cancer patients, there are still some problems of poor prognosis that need to be solved. This study aims to identify the poor prognostic tumor subgroups for the prognostic stratification of ER+ patients.MethodsThrough a comprehensive multi-omics strategy, we systematically characterized the biological and clinical significance of MUCL1+CD24+ cells in breast cancer, and we used multiplex immunohistochemistry to confirm the poor role of MUCL1+CD24+ cells.ResultsSingle-cell transcriptomics unraveled the cellular ontogeny and immune microenvironment interactions of this subset, while bulk RNA sequencing exposed significant pathway heterogeneity and differential immunotherapy responses associated with varying cellular abundance levels. Genomic landscape analysis pinpointed specific somatic mutations correlated with MUCL1(+) CD24(+) cell infiltration patterns, findings that were subsequently validated through multiplex immunohistochemistry to demonstrate strong prognostic value. Crucially, we developed a clinically translatable radiomics approach that successfully correlated specific MRI features with cellular prevalence, establishing a foundation for noninvasive detection of this aggressive cellular subpopulation.ConclusionsThis integrative approach, spanning molecular to imaging analyses, provides novel insights into both the biological drivers and clinical implications of MUCL1(+) CD24(+) cells in breast cancer progression.